DECODING THE UMOD GENE: IMPLICATIONS FOR CHRONIC KIDNEY DISEASE THROUGH GENETIC MECHANISMS, DIAGNOSTICS, AND THERAPEUTIC INNOVATIONS - Tashkenbayeva, Eleonora; Esankulov, Mukhammad (Medical science of Uzbekistan, 2025)
This review examines recent advances in the study of UMOD genetic variations, their functional consequences, and their impact on CKD pathogenesis. It also discusses the potential clinical applications of UMOD as a predictive biomarker for early CKD detection, risk stratification, and targeted interventions. The development of transcriptomic, proteomic, and metabolomic approaches allows for a more comprehensive study of UMOD function and its interactions with other genetic and metabolic pathways. Chronic kidney disease (CKD) is a growing global health concern, affecting millions of people worldwide. Genetic factors play a crucial role in the etiology and progression of CKD, influencing susceptibility, disease severity, and treatment response. Among these factors, the UMOD gene, which encodes the glycoprotein uromodulin, is recognized as a key regulator of kidney function, tubular integrity, and disease susceptibility. UMOD polymorphisms affect kidney function by altering sodium transport, modulating immune responses, and regulating oxidative stress, thereby contributing to hypertension, nephron damage, and CKD progression. Recent GWAS (genome-wide association studies) have confirmed the association between UMOD polymorphisms and an increased risk of CKD and its related complications. Additionally, a significant correlation has been identified between UMOD and hyperuricemia, as uromodulin plays a crucial role in uric acid transport and excretion. Conclusion: Personalized medicine based on UMOD genotyping opens new opportunities for individualized risk assessment, tailored pharmacotherapy, and lifestyle modifications to slow CKD progression. Additionally, promising therapeutic strategies are being developed, including pharmacological modulation of UMOD expression and gene therapy.The integration of genetic knowledge with clinical applications highlights the significance of UMOD in CKD pathogenesis and positions it as a promising target for precision nephrology, potentially improving clinical outcomes and optimizing patient management strategies.